(3QSGdI JhHjN Sgds - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3hUd cJGH GdTjN GdaGVd GdKbI GdCejf GdeaUM Yf Ydeg haVGFdg GdOGd HeVehf ebGhdg Ydi UMI eNGFdg s
(3BNQgG (B:s
(3dCf dg ai GdHYK faG YdjeI JUjQ Zdi GdaQOhS MVQg NUeg fLRJ HefI hdi GdBNQI Je JhHjN Sgd hGdMeO dehdGfG hMOg hGdTcQ ddEeGe GdgGOi YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B79s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds